Parthenocarpy, Cross Pollination and Seed Presence in ‘Afourer’ Mandarin - Gravina, Alfredo; Fornero, Cecilia; Galiger, Sebastián; Inzaurralde, Cristian; Fasiolo, Carolina; Gambetta, Giuliana (Agrociencia Uruguay, 2022)
‘Afourer’ mandarin has been registered as a seedless cultivar. Under Uruguayan productive conditions, in all the evaluated situations, most of the fruits have seeds, which limits its commercial value and marketing. The objectives of this work were to determine ‘Afourer’parthenocarpyc ability and pollination efficiency of four varieties in commercial plantations. Isolation of cross-pollination with nets in two experiments, resulted in 99% of seedlees fruits in Paysandú and 100% in San José. In Paysandú, yield components were similar in openpollination or isolation, demonstrating high parthenocapic ability. Fruit-set in artificial pollination was 40% or more in all cases. Flowers isolated, emasculated and isolated, and pollinated with ‘Afourer’ and isolated resulted in seedlees fruits. The in vitro pollen germination percentage of ‘Afourer’ mandarin and ‘Ortanique’ tangor reached 25%, while ‘Valencia’ orange, ‘Lisbon’ lemon and ‘Nules Clementine’ mandarin, did not exceed 8%. No clear association between these percentages and the number of seeds per fruit was found. The percentage of seeded fruit with artificial pollination was variable, from 18% with ‘Lisbon’ lemon pollen, to 88% with ‘Valencia’ orange pollen. These results can be used for new plantations design and agronomical practices implementation to reduce fruit seed number.